2011
DOI: 10.1007/s11240-011-9937-3
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in the medicinal legume Desmodium motorium (Houtt.) Merr.

Abstract: An efficient protocol was established for regeneration of Desmodium motorium via somatic embryogenesis. Embryogenic calli were induced from cotyledon segments (6 mm, 16 days old) lacking embryo axis, excised from seedlings grown in vitro on Murashige and Skoog (MS) medium supplemented with indole-3-acetic acid (IAA) (2.9 lM) in combination with 6-benzyladenine (BA) (4.44 and 8.88 lM). Differentiation of embryogenic calli into globular and heart-shaped somatic embryos was achieved on transfer to hormone-free MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Addition of BA with various concentrations of IAA or NAA induced adventitious shoots at the cut ends of explants (data not shown), while the explants produced SE directly without an intervening callus when cultured on MS medium supplemented with various concentrations of 2,4-D plus 1.0 mg L -1 BA (Table 1). 2,4-D has been proven to be the most potent auxin and effective for SE induction in most plant species (Chen et al 2010;Konieczny et al 2010;Prange et al 2010;Ratanasanobon and Seaton 2010;Yang et al 2010;Zhang et al 2010;Chai et al 2011;Chitra Devi and Narmathabai 2011;Dai et al 2011) In contrast, SE induction did not occur when the explants were cultured on MS medium devoid of any plant growth regulators. Embryos were induced both light and dark conditions but culturing the explants 2 weeks in the dark followed by 3 weeks under light resulted in high frequency of SE formation.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of BA with various concentrations of IAA or NAA induced adventitious shoots at the cut ends of explants (data not shown), while the explants produced SE directly without an intervening callus when cultured on MS medium supplemented with various concentrations of 2,4-D plus 1.0 mg L -1 BA (Table 1). 2,4-D has been proven to be the most potent auxin and effective for SE induction in most plant species (Chen et al 2010;Konieczny et al 2010;Prange et al 2010;Ratanasanobon and Seaton 2010;Yang et al 2010;Zhang et al 2010;Chai et al 2011;Chitra Devi and Narmathabai 2011;Dai et al 2011) In contrast, SE induction did not occur when the explants were cultured on MS medium devoid of any plant growth regulators. Embryos were induced both light and dark conditions but culturing the explants 2 weeks in the dark followed by 3 weeks under light resulted in high frequency of SE formation.…”
Section: Resultsmentioning
confidence: 99%
“…For most higher plants, 2,4-dichlorophenoxyacetic acid (2,4-D) plays a key role in the induction of somatic embryos (Pinto-Sintra 2007;Othmani et al 2009;Zdravković-Korać et al 2010;Zhang et al 2010;Chitra Devi and Narmathabai 2011). However, previous experiments with Manchurian ash showed that the incorporation of 2,4-D into the medium not only did not stimulate somatic embryogenesis, but also increased the mortality of explants when the compound was applied at a high concentration (data not presented).…”
Section: Discussionmentioning
confidence: 99%
“…The ec obtained from the immature zygotic embryo of pine trees could produce se [ 71 ], but the se production rate was low, and maturation of se was limited. Prolonged culture on the induction medium resulted in an increase in the number of globular and heart-shaped embryos, but did not stimulate the production of mature embryos [ 64 ]. In addition, ec may lose the potential for SE after extended subculture on medium supplemented with 2,4-D.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary embryos originated from the entire surface of the centaury primary cse (Figure 3c,e and Figure 4a-c). In other species, secondary se are formed from different parts of primary se, for example, from cotyledons [38], hypocotyls [63,64], hypocotyl/root zone [57], roots [65], combinations of these organs, for example, from cotyledons and radicles [66], or stomatal guard cells [56].…”
Section: Discussionmentioning
confidence: 99%